Políticas de inovaç\~ao e capacidades estatais comparadas: Brasil, China e Argentina - Ana Célia Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The state capacity to formulate, supervise, and implement (and in some cases to evaluate) science, technology, and innovation policy is the subject of the present work. The goal is to compare state and policy capacity in Brazil, China, and Argentina to point out comparative institutional advantages and disadvantages. One of the study's main conclusions is the existence of a structured consensus on what sectors the enterprising state should incentivize and promote, on where the frontier is located, and whether these countries are at the frontier of innovation depends on: the existence of a rearguard of institutions capable of undertaking prospective (and retrospective) studies that are effectively considered in the decision-making process; the continuous exercise of foresight or technological foresight, subject to processes of periodic revision; the capacity to take account of conflicts of interest, but equally to neutralize them when building structured consensus; and finally to count on a well-established but effective financial innovation system. Two conditions seem important as far as the governance of the modernization process is concerned: visions of the future and state capacities to implement them. What is at issue is not a continuous set of abilities or expertise but a variety of decision-making processes on long-term strategy and coordination in the development and implementation of technology policies.
Keywords: O30; O33; O34; 330; innovation system; developmental state; compared state capacities